One of Nature's Puzzles Is Assembled: Analog of the Earth's Most Complex Mineral, Ewingite, Synthesized in a Laboratory - Tyumentseva, Olga S; Kornyakov, Ilya V; Kasatkin, Anatoly V; Plášil, Jakub; Krzhizhanovskaya, Maria G; Krivovichev, Sergey V; Burns, Peter C; Gurzhiy, Vladislav V (Materials (Basel, Switzerland), 2022)
Through the combination of low-temperature hydrothermal synthesis and room-temperature evaporation, a synthetic phase similar in composition and crystal structure to the Earth's most complex mineral, ewingite, was obtained. The crystal structures of both natural and synthetic compounds are based on supertetrahedral uranyl-carbonate nanoclusters that are arranged according to the cubic body-centered lattice principle. The structure and composition of the uranyl carbonate nanocluster were refined using the data on synthetic material. Although the stability of natural ewingite is higher (according to visual observation and experimental studies), the synthetic phase can be regarded as a primary and/or metastable reaction product which further re-crystallizes into a more stable form under environmental conditions.
Keywords: crystal structure; mineral; structural complexity; topology; nanocluster; X-ray diffraction; ewingite; carbonate; uranyl